A METHOD FOR DETERMINATION OF SEPARATION PROPERTIES OF MEMBRANES - Aleksandar Grujić; Mirko Stijepović; Jasna StajićTrošić; Jovana Ilić; Dragutin Nedeljković (Journal of Engineering & Processing Management, 2015)
In this study, design of lab scale device for determination of separation properties ofmembranes is presented and analyzed. Device operates with different gas pressure betweenchambers, whereby gas streams perpendicular to the membrane. Using appropriate acquisitionsystem and applying mathematical formulas, mechanism for gas transfer through the membrane isdeterminate.Polymer membranes based on zeolite are synthesized and tested by lab scale device. The membraneswith various content of zeolite are tested with CO2 gas until optimal composition of membranecomponents is established. Beside good mechanical and structural properties of applied membrane,suitable values of permeability with good agreement with the literature data are obtained.
Keywords: separation; permeability; membrane; zeolite